2016
DOI: 10.2215/cjn.12981215
|View full text |Cite
|
Sign up to set email alerts
|

Improving Outcomes in Patients Receiving Dialysis: The Peer Kidney Care Initiative

Abstract: The past decade has witnessed a marked reduction in mortality rates among patients receiving maintenance dialysis. However, the reasons for this welcome development are uncertain, and greater understanding is needed to translate advances in care into additional survival gains. To fill important knowledge gaps and to enable dialysis provider organizations to learn from one another, with the aim of advancing patient care, the Peer Kidney Care Initiative (Peer) was created in 2014 by the chief medical officers of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…It is plausible that a concerted effort to improve standards of dialysis care has resulted in a reduced mortality risk, as observed in this large nationwide sample. The Peer Kidney Initiative created in 2014 by the chief medical officers of 14 United States dialysis provider organizations and the Chronic Disease Research Group reported regional variations in the rates of ESRD incidence, hospitalization, and pre-ESRD care, and suggested the possible role of environmental conditions on outcomes in patients receiving maintenance dialysis [38]. Geographic factors that likely affect care, such as socioeconomic fac- tors, environmental factors (e.g., pollution), local factors (e.g., barriers to care), and idiosyncrasies of care delivery systems, are poorly captured in the administrative databases, and future studies are needed to investigate these areas.…”
Section: Discussionmentioning
confidence: 99%
“…It is plausible that a concerted effort to improve standards of dialysis care has resulted in a reduced mortality risk, as observed in this large nationwide sample. The Peer Kidney Initiative created in 2014 by the chief medical officers of 14 United States dialysis provider organizations and the Chronic Disease Research Group reported regional variations in the rates of ESRD incidence, hospitalization, and pre-ESRD care, and suggested the possible role of environmental conditions on outcomes in patients receiving maintenance dialysis [38]. Geographic factors that likely affect care, such as socioeconomic fac- tors, environmental factors (e.g., pollution), local factors (e.g., barriers to care), and idiosyncrasies of care delivery systems, are poorly captured in the administrative databases, and future studies are needed to investigate these areas.…”
Section: Discussionmentioning
confidence: 99%
“…For example, we found a twofold difference between regions in predialysis access to a nephrologist and AVF placement and a more than fourfold difference in incident mortality. Variation in care may be related to historical, social, cultural, economic, demographic, or other features, such as climate or geologic features; controlling for such factors may be difficult analytically, and some comparisons may not be analytically sound (5). It may even be unrealistic to expect outcomes to improve equally across regions, even if the aspiration is laudable.…”
Section: Discussionmentioning
confidence: 99%
“…[133][134][135][136][137][138][139] Recent data indicate that although all-cause mortality rates in haemodialysis patients have been decreasing, the rates of SCD remain the same, indicative of an increased proportion of patients dying from SCD. 140 Risk of all-cause mortality is substantially higher in dialysis (15-20% at 1 year) than in heart failure or post-infarction patients (3-8% at 1 year). [140][141][142][143] Annual risk of SCD is higher in haemodialysis patients in comparison to other patient populations (Figure 4): 5-7% in haemodialysis patients, 4% in heart failure patients, and 1.5-2.7% in non-dialysis patients.…”
Section: Prevention Of Sudden Cardiac Deathmentioning
confidence: 97%
“…140 Risk of all-cause mortality is substantially higher in dialysis (15-20% at 1 year) than in heart failure or post-infarction patients (3-8% at 1 year). [140][141][142][143] Annual risk of SCD is higher in haemodialysis patients in comparison to other patient populations (Figure 4): 5-7% in haemodialysis patients, 4% in heart failure patients, and 1.5-2.7% in non-dialysis patients. The annual rates in non-dialysis patients are comparable to that of post-infarction patients.…”
Section: Prevention Of Sudden Cardiac Deathmentioning
confidence: 97%
See 1 more Smart Citation